Economic Impacts of Global Warming : The Case of the Barents Sea Fisheries - Eide, Arne (Rocky Mountain Mathematics Consortium, 2007)
This article is part of Arne Eide's doctoral thesis, which is available in Munin at http://hdl.handle.net/10037/2399 Regional analyses of possible physical and biological effects of global warming in the Barents Sea area have been carried out recently. Based on such studies possible economic impacts of global warming on the Barents Sea fisheries have been quantified, assuming different types of management regimes. The EconSimp2000 model, consisting of the ecosystem model AggMult and the fleet model EconMult have been parameterized based on fleet and catch records from the Norwegian Barents Sea fisheries. The model has been used to study biological and economic impacts of different environmental scenarios representing possible consequences of global warming. The current environmental situation, including normal seasonal and other variations, has been used as a reference scenario. Several biological and economic indicators have been defined in order to evaluate the simulation results of different environmental scenarios and different types of management regimes. The findings support earlier studies where biological and economic impacts of changes in management regime is found to be more pronounced than impacts caused by effects of global warming.